Recent advances in iatrogenesis of the bile duct main in conventional cholecystectomy - Gilardoni Chedubeau, Federico (Cirugía del Uruguay, 2006)
Objective. To report on an anatomical condicion which is dangerous in surgical procedures and is the cause of the majority of serious iatrogenic accidents of main biliary duct when performing a cholecystectomy.